Evaluación del impacto del vidrio reciclado modificado con Zmembrana en las propiedades mecánicas de bloques de concreto - Rojas Jaimes, Cristel Marisol; Arboleda Briceño, Jose Antonio Andre; Murga Torres, Emzon Enrique; Diaz Malpartida, Isaí Nelson David; Noriega Vidal, Eduardo Manuel; Rodriguez Beltran, Eduar Jose (LACCEI, 2024)
This study aimed to enhance the compressive strength of concrete blocks by incorporating recycled glass and Zmembrana. The primary objective was to investigate the influence of both additives on the compressive strength of concrete blocks. The methodology employed was quantitative, applied, and quasiexperimental in nature. The sample consisted of 144 concrete blocks with varying percentages of recycled glass (0%, 10%, 15%, and 20%) and Zmembrana layers (0, 1, 2, and 3). The blocks were cured for 7, 14, and 28 days and subjected to compressive strength tests. The highest compressive strength was achieved at 28 days of curing for concrete blocks with 15% recycled glass and 1 layer of Zmembrana applied with a brush after demolding, reaching a strength of 53.20 kg/cm2. The results demonstrate the beneficial effects of incorporating recycled glass and Zmembrana in enhancing the compressive strength of concrete blocks